The artist's way : workbook - Cameron, Julia, ....- (London : Souvenir press, 2020)
For the millions of people who have uncovered their creative selves through The Artist's Way: a workbook and companion to the international bestseller. In this elegantly redesigned and user-friendly volume you'll find: - More than 110 Artist's Way tasks - More than 50 Artist's Way check-ins - Insights into the creative process - New ideas for Morning Pages and Artist's Dates The Artist's Way Workbook is an indispensable book for anyone following the path to creativity laid out in The Artist's Way.
Keywords: Art; Creativity